Essays on firm level responses to trade and foreign direct investment liberalization in India - Lancheros, Sandra (2012)
During the past three decades policy makers from a number of developing countries have undertaken outward-oriented economic reforms with the objective of stimulating global capabilities and allowing domestic firms to catch up with the technological frontier. In the case of India, one of the most important features of such economic reforms has been the promotion of exports and outward foreign direct investments (FDI). Using a rich set of econometric methodologies, we examine the forces underlying Indian firms’ global strategies in the form of exporting and investing abroad and the impact of such decisions upon their future performance. Our analysis covers the years from 1999 to 2007, a period of gradual internationalization of Indian firms in response to ongoing trade and FDI liberalization. We contrast the strategies followed by manufacturing and service firms and pay particular attention to the role of technological and financial factors in shaping firms’ globalization processes.